Natural antisense transcripts as drug targets - Khorkova, Olga; Stahl, Jack; Joji, Aswathy; Volmar, Claude-Henry; Zeier, Zane; Wahlestedt, Claes (Frontiers in Molecular Biosciences, 2022)
The recent discovery of vast non-coding RNA-based regulatory networks that can be easily modulated by nucleic acid-based drugs has opened numerous new therapeutic possibilities. Long non-coding RNA, and natural antisense transcripts (NATs) in particular, play a significant role in these networks engaging a wide variety of disease-relevant biological mechanisms such as transcription, splicing, translation, mRNA degradation and others. Currently, significant efforts are dedicated to harnessing these newly emerging NAT-mediated biological mechanisms as drug targets for translation to the clinic. This review will highlight the recent clinical and pre-clinical developments in this field and survey the advances in nucleic acid-based drug technologies that make these developments possible.